Saccharomyces cerevisiae from Brazilian kefir-fermented milk: An in vitro evaluation of probiotic properties - Lima, Meire dos Santos Falcão de (2017)
The therapeutic use of probiotics for supporting the antibiotic action against gastrointestinal disorders is a current trend and emerging applications have gained popularity because of their support for various microbiological activities in digestive processes. Microorganisms isolated from kefir with great probiotic properties, in addition to high resistance to harsh environmental conditions, have been widely researched. Administration of probiotic yeasts offers a number of advantages, when compared to bacteria, because of particular characteristics as their larger cell size. In the present study, 28 strains of Saccharomyces cerevisiae were isolated, after in vitro digestion of kefir-fermented milk, and identified by molecular based approaches. A screening was performed to determine important quality requirements for probiotics including: antagonistic and antioxidant activities, -galactosidase synthesis, autoaggregation, surface hydrophobicity and adhesion to epithelial cells. The results showed strains: with antagonistic activity against microbial pathogens such as Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus subtilis; able to produce -galactosidase; with antioxidant activity levels higher than 90%; with hydrophobicity activity and autoaggregation ability (evaluated by adhesion test, where all the strains presented adhesion to mice ileal epithelial cells). These findings are relevant and the strains are recommended for further in vivo studies as well as for potential therapeutic applications.